CAN RIGID GAS PERMEABLE (RGP) CONTACT LENS BE THE BEST OPTION FOR A KERATOCONUS PATIENT? Poster Presentation - Case Report - Resident - DINA FATMA DWIMARTA; ANI ISMAIL; EVA KUMALASARI (Majalah Oftalmologi Indonesia, 2023)
Introduction : Keratoconus is a condition of cone-shaped cornea caused by stromal thinning. This disorder leads to visual disturbance due to irregular astigmatism, myopia, and corneal protrusion. A severe irregular astigmatism must be corrected by rigid gas permeable (RGP) contact lenses. Case Illustration : A 29 y.o female visited Ophthalmologist Clinic Subdivision of Refraction, Contact Lens, and Low Vision in RSKMM Provinsi Sumsel, complaining of discomfort while using her current glasses. Anamnesis, physical examination, and ophthalmologic examination were carried out. The patient then was maximally corrected of her refractive status, followed by contact lenses fitting and post- fitting evaluation. Discussion : Early ophthalmologic examination showed visual acuity of 6/60 ph 6/9 on both eyes. Corneal topography evaluation confirmed pattern of bilateral keratoconus, each 78% on right eye and 87% of left eye. Best-corrected visual acuity was 6/6 using S-3.50 C-7.00 180? (right eye) and S-4.00 C-6.00 170? (left eye). RGP fitting test was carried with trial lenses of S-4.00 D for both eyes with both base curve of 7.2 mm and diameter of 9.2 mm. Over-refraction showed result of S-3.50 D (right eye) and S-3.75 D (left eye) for both eyes to reach visual acuity of 6/6 and for patient to feel comfortable. Conclusion : While some period of adaptation was needed, severe keratoconus should be treated using RGP contact lenses to achieve a better prognosis. Accurate fitting test of RGP resulting in comfortable and satisfied outcome of patient.